2000
DOI: 10.1089/cbr.2000.15.15
|View full text |Cite
|
Sign up to set email alerts
|

Pretargeted Radioimmunotherapy (PRIT™) for Treatment of Non-Hodgkin's Lymphoma (NHL): Initial Phase I/II Study Results

Abstract: Pretargeted radioimmunotherapy (PRIT) was investigated in patients with non-Hodgkin's lymphoma (NHL). The PRIT approach used in this study is a multi-step delivery system in which an antibody is used to target streptavidin to a tumor associated antigen receptor, and subsequently biotin is then used to target 90Y radioisotope to the tumor localized streptavidin. A chimeric, IgG1, anti-CD20 antibody, designated C2B8 or Rituximab, was conjugated to streptavidin (SA) and administered to patients with NHL. Thirty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 6 publications
2
65
0
3
Order By: Relevance
“…Therapeutic studies showed that 70-100% of xenografted mice were cured with 90 Y-DOTA-biotin, and the toxicity was significantly lower when compared with 90 Y directly labeled intact antibodies. Clinical trails also validated the feasibility of the Pretarget approach (19)(20)(21)(22).…”
mentioning
confidence: 80%
“…Therapeutic studies showed that 70-100% of xenografted mice were cured with 90 Y-DOTA-biotin, and the toxicity was significantly lower when compared with 90 Y directly labeled intact antibodies. Clinical trails also validated the feasibility of the Pretarget approach (19)(20)(21)(22).…”
mentioning
confidence: 80%
“…9 In addition, a pilot study introducing a novel 'pretargeting' strategy of two-step radioimmunotherapy using streptavidin-labeled anti-CD20 antibodies was recently published. 10 A different way to improve mAbs effects is to conjugate them to a toxic moiety, in order to obtain immunotoxins, chimeric proteins with specific cytotoxic effect. To this purpose, a variety of bacterial and plant toxins have been utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, renal toxicity remains a concern when using this strategy. Using this latter motif, a Phase I/II trial was conducted that treated NHL patients with rituximab-SA conjugate injected sequentially, followed by a clearing agent (biotin-N-acetyl-glucosamine) and thereafter with 30 or 50 mCi per m 2 of 90 Y-DOTAbiotin 86 . Patients responded favourably, with only transient haematological toxicities.…”
Section: Resultsmentioning
confidence: 99%